Dashboard Monitoring Renstra Dan Renop Jurusan Teknik Elektro Politeknik Negeri Semarang - Ningsih, Maharani Prastuti; Rahardjo, Parsumo; Nugroho, Ari Sriyanto (JTET (Jurnal Teknik Elektro Terapan), 2017)
Each department at the Polytechnic of Semarang has a Strategic Plan (Plan) and the Operational Plan (RENOP) to manage and monitor the progress of each department. One department is the Department of Electrical Engineering. In pengeleloaan strategic planning and RENOP done through an information system that is equipped with a Dashboard. Dashboard is intended to help the Department of Electrical Engineering in order to more easily in monitoring targets and achievements in strategic planning and RENOP. Dashboard development is done using the waterfall method (waterfall), starting from analysis, design, writing code, testing and maintenance. This application uses a client-server architecture. The system comes with features designed to simplify the user in seeing how the development of each unit. Users will be facilitated in terms of readability of data and given an attractive appearance so that they can easily understand what is in the data. Testing the system using the method of testing each unit function of each feature. The results of this research is an information system that can help the department head, the department secretary, and the chairman of the study program in monitoring the Strategic Plan and RENOP. Meanwhile, user satisfaction test Dashboard Monitoring and Strategic Planning Department of Electrical Engineering RENOP conducted by filling the questionnaire obtained results of 81.2%, which means that the users were satisfied with the application of Strategic Planning and Monitoring Dashboard RENOP Department of Electrical Engineering.Keywords: client-server, dashboard, waterfall